(untitled) (Journal of the College of Basic Education, 2026)
This research examines the effectiveness of contemporary ceramic façades as a material and visual system that contributes to reshaping the architectural identity of buildings, going beyond the traditional function of the façade as merely an external envelope. The research problem arises from questioning the extent to which ceramics, as a technologically developed contemporary material, can produce a visual and aesthetic discourse within the formation of spatial experience that interacts with place, human presence, and the urban context. The research aims to identify the effectiveness of ceramic façades in architectural space and to analyze their role in shaping spatial experience and enriching the contemporary architectural scene. The first chapter also includes a definition of the key terms of the research. The second chapter addresses the theoretical framework and previous studies, and is composed of three sections. The first section discusses industrial ceramics and their technological transformations in architectural applications. The second section examines the ceramic façade as a visual medium for constructing contemporary architectural identity. The third section addresses digital technologies and their impact on the reformulation of contemporary ceramic façades. The chapter concludes with indicators derived from the theoretical framework and previous studies.The third chapter presents the research procedures. It includes the research population, which consists of (15) models, from which a sample of (3) models was intentionally selected to cover the research boundaries, adopting the descriptive method to analyze the research sample.The fourth chapter presents the results, discussion, conclusions, recommendations, and proposals, which reflect ideas and implications based on the applications of the effectiveness of ceramic façades in architectural space. Among the most important results reached by the researcher: The ceramic façade is capable of performing the role of a cultural mediator, as it combines the contemporary technological dimension with the symbolic dimension linked to the memory of the material and its history, granting the building an identity dimension that goes beyond purely formal characteristics. Among the most important conclusions 1It can be concluded that contemporary ceramic façades represent a qualitative transformation in architectural thought, shifting from the logic of superficial decoration to the logic of integrated visual and environmental effectiveness